Tindak Tutur Ilokusi Direktif Bertanya dengan Kinesik Gestural dalam Film “Sekawan Limo” Karya Bayu Skak (Kajian Pragmatic) - De Ajeng Putri Rahmawati (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
Directive illocutionary acts involving questions are commonly encountered in everyday life and are also present in a film that depicts everyday life. This will be examined in this study, focusing on the film “Sekawan Limo” by Bayu Skak. The film features a variety of languages and is dominated by Javanese, which is a distinctive feature of the film. This study discusses direct questioning (confirmation and the use of the words what, who, how, why, how much, when) and indirect questioning (rhetorical, commands, insults, reminders, and tests) Questioning is also supported by gestural kinesics that reinforce verbal communication and take the form of bodily behavior or actions. This study employs a pragmatic analysis. The research method used is qualitative descriptive. The data for this study consists of character dialogues in the film “Sekawan Limo.” The primary data of this study comprises utterances classified as directive illocutionary acts of questioning, supported by gestural kinesics. The research instrument in this study is the researcher themselves. The results of this study consist of text and images that will be explained in accordance with the researcher’s findings and based on the theory employed.